2023
DOI: 10.1039/d2mh01073a
|View full text |Cite
|
Sign up to set email alerts
|

High-strength, low infrared-emission nonmetallic films for highly efficient Joule/solar heating, electromagnetic interference shielding and thermal camouflage

Abstract: High-strength nonmetallic material with low infrared (IR) emission is rare in nature yet highly anticipated especially in military and aerospace fields for thermal camouflage, infrared stealth, energy-saving heating. Here, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…39,40 As a result, even MP0 presented a high absorption of 85.8% on average over the AM 1.5G solar spectrum. Note that Ti 3 C 2 T x has been recently reported as an infrared white material with a low infrared emissivity of about 10%, 41,42 which further verified that the absorption of sunlight could be largely enhanced by assembling Ti 3 C 2 T x nanosheets into porous non-woven fabric with micro-crumples. The highest absorption was realized by MP2, which could reach 88.3% on average.…”
Section: Resultsmentioning
confidence: 58%
“…39,40 As a result, even MP0 presented a high absorption of 85.8% on average over the AM 1.5G solar spectrum. Note that Ti 3 C 2 T x has been recently reported as an infrared white material with a low infrared emissivity of about 10%, 41,42 which further verified that the absorption of sunlight could be largely enhanced by assembling Ti 3 C 2 T x nanosheets into porous non-woven fabric with micro-crumples. The highest absorption was realized by MP2, which could reach 88.3% on average.…”
Section: Resultsmentioning
confidence: 58%
“…Zhang et al [ 175 ] have suggested that wave interference occured during the course of multiple reflections, and its possible resonance characteristics would promote the absorption of specific electromagnetic waves ( Figure 27 f). Wang et al [ 177 ] prepared a shielding material with a layered structure of conductive pearls. When an electromagnetic wave reached the surfaces of the conductive pearls, it would interact with the carrier wave on the surface of MXene and thus become partially reflected.…”
Section: Mechanism Of Membrane Shielding Materialsmentioning
confidence: 99%
“…Copyright 2020, Elsevier. ( g ) Schematic diagram of the EMI shielding mechanism of conductive pearls [ 177 ]. Copyright 2022, Wiley.…”
Section: Figurementioning
confidence: 99%
“…For radar stealth, MAMs are the core to absorb microwaves to achieve radar stealth. Toward infrared stealth, two main methods are always employed: one is to reduce the infrared emission rate of the target, − such as the method of attaching a layer of coating on the target; the other is to reduce the temperature of the target, such as the method of attaching a heat insulation layer on the target …”
Section: Functionalization Of Microwave Absorption Materialsmentioning
confidence: 99%